Interaction between Uneven Cavity Length and Shaft Vibration at the Inception of Synchronous Rotating Cavitation - Y. Yoshida; Y. Kazami; K. Nagaura; M. Shimagaki; Y. Iga; T. Ikohagi (International Journal of Rotating Machinery)
Asymmetric cavitation is known as one type of the sources of cavitation induced vibration in turbomachinery. Cavity lengths are unequal on each blade under condition of synchronous rotating cavitation, which causes synchronous shaft vibration. To investigate the relationship of the cavity length, fluid force, and shaft vibration in a cavitating inducer with three blades, we observed the unevenness of cavity length at the inception of synchronous rotating cavitation. The fluid force generated by the unevenness of the cavity length was found to grow exponentially, and the amplitude of shaft vibration was observed to increase exponentially. These experimental results indicate that the synchronous shaft vibration due to synchronous rotating cavitation is like selfexcited vibrations arising from the coupling between cavitation instability and rotordynamics.